2016
DOI: 10.1097/shk.0000000000000615
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Venous Waveform Analysis for Detecting Hemorrhage and Iatrogenic Volume Overload in a Porcine Model

Abstract: In this study, PIVA demonstrated a greater sensitivity for detecting acute hemorrhage, return to euvolemia, and iatrogenic fluid overload compared with standard monitoring and SI. PIVA may provide a low-cost, minimally invasive monitoring solution for monitoring and resuscitating patients with perioperative hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 30 publications
(21 reference statements)
2
38
0
1
Order By: Relevance
“…One of the earliest methods of venous waveform capture was via direct transduction using a peripheral intravenous catheter connected to a pressure transducer. 1 , 2 , 6 , 7 Furthermore, a piezoelectric sensor placed on the volar aspect of the wrist, directly over the superficial veins, has also allowed for non-invasive capture of the peripheral venous waveform. 3 , 4 , 16 , 17 The piezoelectric sensor is connected to a control box that amplifies the venous waveform detected from vibrations related to the low amplitude pulsatile flow of venous blood.…”
Section: Methods Of Venous Waveform Acquisitionmentioning
confidence: 99%
“…One of the earliest methods of venous waveform capture was via direct transduction using a peripheral intravenous catheter connected to a pressure transducer. 1 , 2 , 6 , 7 Furthermore, a piezoelectric sensor placed on the volar aspect of the wrist, directly over the superficial veins, has also allowed for non-invasive capture of the peripheral venous waveform. 3 , 4 , 16 , 17 The piezoelectric sensor is connected to a control box that amplifies the venous waveform detected from vibrations related to the low amplitude pulsatile flow of venous blood.…”
Section: Methods Of Venous Waveform Acquisitionmentioning
confidence: 99%
“…With this innovative technology, the venous waveform is amplified and the lower frequencies that correspond to the pulse rate, and its harmonics (multiples of the pulse rate) are analyzed based on the ratiometric relationship of their respective amplitudes to hemodynamic volume changes. The result of said analysis is a NIVA value-an adjusted numerical value initially developed in adult patients undergoing elective right heart catheterization and considered to be "equivalent" to the clinical gold standard of volume status, pulmonary capillary wedge pressure [12,13]. A recent study in adults showed that the NIVA value correlated linearly with blood loss and with the hemodynamic indices [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies that have analyzed harmonics of the heart rate frequency in the frequency domain of the venous waveform have revealed that the relative power contributions of the pulse rate and its harmonics change with volume and can be quantified into a value that is representative of volume status. [1][2][3][4][5][6] Non-Invasive Venous waveform Analysis (NIVA) is an innovative, non-invasive method of capturing the peripheral venous waveform for analysis using a piezoelectric sensor connected to a control box (Figure 1). The piezoelectric sensor is applied to the skin directly over the superficial veins of the wrist and captures small deflections in the skin that occur as a result of the pulsatile venous waveform.…”
Section: Introductionmentioning
confidence: 99%